Problems of Managing Potato Plant Growth Under Micropropagation for Primary Seeds - Kornatskiy , Sergey (KnE Life Sciences, 2021)
This study shows the possibility of controlling the growth of potato microplants when adding the Murashige-Skoog (MS) nutrient medium chlorocholine chloride (CCC) to the composition at a concentration of 0.05-0.25 mg ⋅ L −1. Varietal specificity of the reaction of potato plants to the preparation was revealed. At optimal concentrations of CCC, plants with a stem length of 7-10 cm in 250 ml flasks were grown from single-node microcuttings for 1.5 months. Microplants were removed from the flasks using 20 cm scissors and unsterilized tweezers. The roots were shortened to 2-3 mm and the basal part of the stems was treated with a chalk-based paste containing 0.04% indolylbutyric acid (IBA). Plants were planted on 36 mm diameter Jiffy 7 peat pellets directly in the laboratory. The trays with the material were transferred to the greenhouse at the end of April at a temperature of 20-25 °C and placed in the conditions of the upper fine irrigation. After 3-4 days, mass root formation began in the plants, and another week later the seedlings were ready for use. By then the height of the plants was 10-15 cm, and the roots were clearly visible on the surface of the peat pellets. Planting these seedlings in a technological greenhouse to obtain minitubers was convenient and inexpensive. Keywords: potato, microcuttings, microtubers, minitubers, chlorocholine chloride, peat pellets